2019
DOI: 10.3390/biomimetics4040076
|View full text |Cite
|
Sign up to set email alerts
|

Design, Manufacturing, and Testing of a New Concept for a Morphing Leading Edge using a Subsonic Blow Down Wind Tunnel

Abstract: This paper presents the design and wind tunnel test results of a wing including a morphing leading edge for a medium unmanned aerial vehicle with a maximum wingspan of 5 m. The design of the morphing leading edge system is part of research on the design of a morphing camber system. The concept presented here has the advantage of being simple to manufacture (wooden construction) and light for the structure of the wing (compliance mechanism). The morphing leading edge prototype demonstrates the possibility of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The Research Laboratory in Active Controls, Avionics, and AeroServoElasticity (LARCASE) team is studying several approaches for reducing fuel consumption [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], including the use of morphing wing technologies, such as the morphing leading edge prototype demonstrates the possibility of modifying the stall angle of the wing. It was shown that the stall angle of the wing was delayed using a downward deformation of the leading edge [ 17 , 18 ]. An experimental and numerical analysis was carried out for a UAS-S45 wing geometry with the aim to improve the laminar flow on the upper surface of the wing, between 10% and 70% of the chord [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Research Laboratory in Active Controls, Avionics, and AeroServoElasticity (LARCASE) team is studying several approaches for reducing fuel consumption [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], including the use of morphing wing technologies, such as the morphing leading edge prototype demonstrates the possibility of modifying the stall angle of the wing. It was shown that the stall angle of the wing was delayed using a downward deformation of the leading edge [ 17 , 18 ]. An experimental and numerical analysis was carried out for a UAS-S45 wing geometry with the aim to improve the laminar flow on the upper surface of the wing, between 10% and 70% of the chord [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Communier and co-workers experimentally and numerically demonstrated that morphing leading edge concepts can potentially replace traditional leading-edge devices in terms of their aerodynamic properties [9]. However, for the design of a morphing leading edge, the aerodynamic efficiency is not solely important.…”
Section: Introductionmentioning
confidence: 99%